Assessing Fire Resistance Through One-Dimensional Charring Rates of Solid Malaysian Light Hardwoods Using The Reduced Cross-Section Method - Hafizah Muhamad Azlan,; Norshariza Mohamad Bhkari,; Zakiah Ahmad,; Lannie Francis, (International Journal of Integrated Engineering, 2025)
In recent decades, timber structures have become popular for their environmental benefits and support of sustainable development goals. They reduce energy demands and pollution hence making the construction sector greener. However, timber is a combustible material, make its use in structural applications is limited by building regulations, especially for taller and larger buildings due to fire safety concerns. Therefore, studying the fire resistance and structural integrity of timber during and after a fire is crucial. This paper presents a study examining the fire performance of timber beams made from Malaysian tropical light hardwoods. To assess the performance in detail, the char depth of timber beams was determined by using the reduced cross-section method for various species, ranging from light hardwoods with densities varying from 450 kg/m³ to 700 kg/m³. The beams were tested under one-dimensional fire conditions for varying durations (45 min, 60 min, and 70 min) using standard fire exposure. The charring rate value, ßo also been evaluated for these species. The findings show that certain species have shown charring rates of 0.5 mm/min, which align with the guidelines set out in Eurocode 5 for solid hardwoods with timber densities above 450 kg/m³.